Validity of Bitcoin Transactions in the Perspective of Cross Schools of Fiqh (Sophist: Jurnal Sosial Politik Kajian Islam dan Tafsir, 2024)
This research aims to explore bitcoin as an online payment system of peer-to-peer electronic money sent directly from one party to another without going through financial institutions. The existence of bitcoin as a virtual currency is considered legal, or allowed with conditions, namely if it is recognised by the state. The rights and obligations to manage iqtishadiah including the issuance of new currencies are the authority of the state. In this research, all factors, both oral and written, from data sources have been taken and presented to answer the problems in the research. Therefore, this research is a type of descriptive research, which is research that makes a description of situations or events. In this case, bitcoin is not issued by the state and is not recognised by the Indonesian bank, so bitcoin is a currency that is considered illegal in Indonesia. The concept of bitcoin according to classical scholars and contemporary scholars includes: first, bitcoin in function is the same and there is no difference. Second, the content of bitcoin legality is illegal currency in Indonesia. Third, the weakness side can be used as a money laundering tool. Bitcoin is a digital currency that can be used by developed countries. This currency is haram li ghairihi, because the violation is caused by something else, not the substance of bitcoin itself.